Odpowiedzi

2009-12-02T19:08:09+01:00
A)2x-y=5
-y=5-2x
y=-5+2x
b)1/3y=x-3
y=(x-3)÷1/3
y=(x-3)*3
y=3x-9
c)3(x-y)=2x
3x-3y=2x
-3y=2x-3x
-3y=-x
y=x/3
2009-12-02T19:08:25+01:00
A) 2x-y=5 /+2x
y=5+2x

b) 1/3y= x-3 /*3
y=x-3*3

c) 3(x-y)=2x /:3
x-y=2x:3 /+x
y=3x:3
Najlepsza Odpowiedź!
2009-12-02T19:11:11+01:00
A) 2x-y=5/-2x

-y= 5-2x/*(-1)

y= -5+2x

b) 1/3y= x-3/*3
y=3*(x-3)
y=3x-9

c) 3(x-y)=2x
3x-3y=2x/-3x
3y=-x/:3
....x...................1
y= --- może być też --*x
....3...................3

Pozdro :D